Preparation of Clay Minerals – Natural Surfactant Composites to Remove Organic Dyes and Heavy Metals - Laysandra, Livy; Kurniawan, Darwin; Soetaredjo, Felycia Edi; Ismadji, Suryadi (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2023)
The rapid development of industry is considered to be the main cause of various environmental problems, which are mainly caused by the discharge of wastewater which contains many hazardous compounds. Dyes and heavy metals are type of hazardous substances that are often found in industrial wastewater and cause ecosystem damage. Dyes and heavy metals are more difficult to remove due to their inability to be broken down, so they can build up and reach dangerous levels. Adsorption is a straighforward and efficient method for dealing with hazardous substance contamination in water. Clay minerals, known for their efficient adsorption properties, were chosen for this procedure. Clay minerals are porous materials so they are suitable for use as adsorbents. The intercalation technique is a robust strategy to further increase the adsorption capacity of clay minerals, which is done by treating clay minerals with surfactants. Clay minerals modified with natural surfactants are considered as a potential choice for removal procedures. The use of this natural surfactant was chosen because of its excellent adsorption capacity and environmentally friendly properties. Polar lipids, natural surfactants, are commonly present in the lipid layers of plants and animals. This review focuses on the synthesis of modified clay minerals using different natural surfactants such as soybeans, saponins, lipopeptides, and rhamnolipids, as well as the use of alternative clay mineral/natural surfactant composites. This review describe various types of natural surfactants that can be used to modify clay minerals and their application in the adsorption process.